The relevance of the formation of cost accounting for loans on the basis of IFRS in business entities - Khushvaqtova Nozanin Nurbek qizi (Zien Journals, 2022)
The implementation of International Financial Reporting Standards (IFRSs) will improve the internal management system of business entities through the use of uniform methods of accounting, provide information to stakeholders about the financial condition of the enterprise and increase the company's competitiveness. This article illustrates the relevance of applying the IFRS to our national accounting system today.
Keywords: IFRS; IAS 323; IFRS 24; Borrowing Expenses